Character patterns according to Freiburg classification and its relationship to self - realization of players participating in the Championship Mustansiriya University volleyball - Abed Al- Janabi, Saad Abbas; Finjan, Raad Abdul Amir; Dwiger, Mehdi Ali (International Journal of Psychosocial Rehabilitation, 2020)
The game of volleyball is a sport that has gained popularity recently and is practiced in various countries of the world, whether by men or women and become held for the official world tournaments and is one of the games that have the skills and requirements that can be seen by all who watch their games. Attention to the player's personal qualities has emerged as a subject that is the cornerstone that concerns the player's processes of regulating the player's behavior, through which he becomes increasingly aware of his psychological dimension, and which focuses on his behavior from himself and others in the house, street, stadium and classroom. Self-knowledge includes a focus on the hidden aspects of the personality and people are more certain of their cognitive processes, beliefs, moods, feelings and others as self-study is concerned with the social appearance and the type of impression that the individual leaves others and their beliefs.